The influence of internal service quality factors on employee’s productivity / Fatin Nursyamimi Salman and Nurul Atikah Awg Hamat - Salman, Fatin Nursyamimi; Awg Hamat, Nurul Atikah (2018)
Employee’s productivity is the efficiency and effectiveness of the employees’ job behaviors that directly and indirectly contribute to the organizational work goals (Taylor, Steel & Simon, 2013). At the individual level, productivity is the measurement tracks how well the worker applies talents and skills, using materials and equipment to produce products and services within a specified time period. According to Tahir, Yousafzai, Jan & Hashim (2014), productivity refers to the accomplishment of something or mere working effectiveness. In an organization, productivity is realized at the levels of organization, process and individuals and interrelationships among these will define the vantage points of the organization. Employee’s productivity can make the organization achieves the organization goals. The main objective of organization is wants to improve the employee’s productivity when doing their work as it will make the organizational performance better